2013
DOI: 10.1016/j.bmcl.2012.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Phthalazinone inhibitors of inosine-5′-monophosphate dehydrogenase from Cryptosporidium parvum

Abstract: Cryptosporidium parvum (Cp) is a potential biowarfare agent and major cause of diarrhea and malnutrition. This protozoan parasite relies on inosine 5′-monophosphate dehydrogenase (IMPDH) for the production of guanine nucleotides. A CpIMPDH-selective N-aryl-3,4-dihydro-3-methyl-4-oxo-1-phthalazineacetamide inhibitor was previously identified in a high throughput screening campaign. Herein we report a structure-activity relationship study for the phthalazinone-based series that resulted in the discovery of benzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
1
40
0
1
Order By: Relevance
“…In as much as they, harbor a wide variety of parasites which can be detrimental to their and human health (Calvete et al 1998;Hille et al 2014;Krecek et al 2010;Ramos et al 2013;Scorza et al 2011;Silaghi et al 2014), and also represent potential reservoirs of helminthic parasites to domestic cats and human, especially in urban areas (Hille et al 2014;Polak et al 2014;Youssef and Uga 2014). Besides, due to their contact with both domestic cats and humans, stray cat may play an important role in the transmission of several pathogenic agents; such as Toxoplasma gondii (Can et al 2014;Lappin 2010;Vilares et al 2014) and Cryptosporidium (Bush et al 2011;Scorza et al 2011;Spada et al 2013;Spain et al 2001) that have the ability to cause life-threatening infections in individuals (Davoust et al 2014;Johnson et al 2013), or Leishmania infantum (Chatzis et al 2014;Hatam et al 2010;Pennisi et al 2013;Richter et al 2014) and Toxocara spp. which have been associated with two main clinical syndromes in humans (ocular larva migrans and visceral larva migrans) (Bowman et al 2010;Fisher 2003;Petithory 2007;Prokopowicz and Sosnowska 1990;Rubinsky-Elefant et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In as much as they, harbor a wide variety of parasites which can be detrimental to their and human health (Calvete et al 1998;Hille et al 2014;Krecek et al 2010;Ramos et al 2013;Scorza et al 2011;Silaghi et al 2014), and also represent potential reservoirs of helminthic parasites to domestic cats and human, especially in urban areas (Hille et al 2014;Polak et al 2014;Youssef and Uga 2014). Besides, due to their contact with both domestic cats and humans, stray cat may play an important role in the transmission of several pathogenic agents; such as Toxoplasma gondii (Can et al 2014;Lappin 2010;Vilares et al 2014) and Cryptosporidium (Bush et al 2011;Scorza et al 2011;Spada et al 2013;Spain et al 2001) that have the ability to cause life-threatening infections in individuals (Davoust et al 2014;Johnson et al 2013), or Leishmania infantum (Chatzis et al 2014;Hatam et al 2010;Pennisi et al 2013;Richter et al 2014) and Toxocara spp. which have been associated with two main clinical syndromes in humans (ocular larva migrans and visceral larva migrans) (Bowman et al 2010;Fisher 2003;Petithory 2007;Prokopowicz and Sosnowska 1990;Rubinsky-Elefant et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the exclusive reliance on the salvage pathway by Cryptosporidium and its high metabolic demand for nucleotides due to the parasite's complicated lifecycle make IMPDH a potential drug target candidate. This hypothesis is supported by the recent discovery of several Cryptosporidium IMPDH inhibitors Johnson et al, 2013;Maurya et al, 2009;Sharling et al, 2010;Umejiego et al, 2008).…”
Section: Introductionmentioning
confidence: 80%
“…Despite this, efforts to develop new and more effective treatments for this disease have been hindered by (1) lack of suitable targets and (2) lack of target validation and transfection tools. The completion of the Cryptosporidium genome (Abrahamsen et al, 2004;Xu et al, 2004), which resulted in a range of potential drug targets being identified, has overcome the first hindrance and IMPDH is now a well recognised and important drug target Johnson et al, 2013;Maurya et al, 2009;Sharling et al, 2010;Umejiego et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the CpIMPDH gene was obtained from an epsilonproteobacterium by lateral gene transfer and thus is very different from host IMPDHs (30,43). We have developed several structurally distinct classes of CpIMPDH inhibitors, achieving nanomolar potency and selectivity in excess of 1,000-fold versus the human enzymes (44)(45)(46)(47)(48)(49)(50). Here, we report the antiparasitic activity of our eight most promising compounds in the interleukin-12 (IL-12) knockout mouse model.…”
mentioning
confidence: 99%